Lactic acid production from sugarcane bagasse hydrolysates by Lactobacillus pentosus: Integrating xylose and glucose fermentation. (9th October 2018) - Wischral, Daiana; Arias, Johanna Méndez; Modesto, Luiz Felipe; de França Passos, Douglas; Pereira, Nei
Abstract : Lactic acid, traditionally obtained through fermentation process, presents numerous applications in different industrial segments, including production of biodegradable polylactic acid (PLA). Development of low cost substrate fermentations could improve economic viability of lactic acid production, through the use of agricultural residues as lignocellulosic biomass. Studies regarding the use of sugarcane bagasse hydrolysates for lactic acid production by Lactobacillus spp. are reported. First, five strains of Lactobacillus spp. were investigated for one that had the ability to consume xylose efficiently. Subsequently, biomass fractionation was performed by dilute acid and alkaline pretreatments, and the hemicellulose hydrolysate (HH) fermentability by the selected strain was carried out in bioreactor. Maximum lactic acid concentration and productivity achieved in HH batch were 42.5 g/L and 1.02 g/L h, respectively. Hydrolyses of partially delignified cellulignin (PDCL) by two different enzymatic cocktails were compared. Finally, fermentation of HH and PDCL hydrolysate together was carried out in bioreactor in a hybrid process: saccharification and co‐fermentation with an initial enzymatic hydrolysis. The high fermentability of these process herein developed was demonstrated by the total consumption of xylose and glucose by Lactobacillus pentosus, reaching at 65.0 g/L of lactic acid, 0.93 g/g of yield, and 1.01 g/L h of productivity. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2718, 2019